Recrutamento muscular durante a extensão ativa de quadril em prono em indivíduos com dor lombar - Cristiano Queiroz Guimaraes (2007)
Changes in activation patterns of the trunk and hip extensor muscles can result in excessive stress on the lumbar spine structures, predisposing it to lesions and pain. The objective of this study was to compare activation patterns of the gluteus maximus, semitendinosus and erector spinae muscles between asymptomatic and low back pain individuals during active prone hip extension exercises. Fifty individuals were recruited and divided into two groups: 30 asymptomatic (24.5 ± 3.47 years) and 20 with chronic low back pain (28.75 ± 5.52 years). They performed active prone hip extension exercises while the electromyographic activity of the investigated muscles was recorded using an electromyographer and a motion analysis system. No significant differences were found between the groups regarding the latency and amount of muscular activation of the investigated muscles. Muscular activation patterns were similar for both groups, starting with the semitendinosus, followed by the erector spinae, and then, the gluteus maximus. In both groups, a significant delay of the onset of the gluteus maximus was observed. The assessment of activation patterns was not capable of discriminating individuals with and without low back pain, suggesting an overlap of the studied populations.